Design Of Casava Slicer Machine For Improving Casava Chips Industry - Natalia D (Bandar Lampung University (UBL), 2017)
Cassava is a fruit of the plant tubers that grow in the soil. Cassava has a hard texture of the meat.Cassava also be used as a companion in several dishes such as fried foods, spinach village, a variety of snacks, chips and other dishes.The chips are snacks that are popular with the public. The chips are classified as types of food craker foods that are dry and crisp with a high fat content.Cassava cutting machine is a tool to cut cassava into thin sheets with a thickness of ± 1 to 2 mm. Not only that, the machine also can produce pieces with the same thickness, and the cutting time becomes fast.The design is the beginning of a series of activities in the process of making the product. The perancanagna stage made important decisions that affect other activities follow. Thus, before a product is made first made the design process that will produce a drawing or a simple picture of product to be made